Co-Prevalence of Quinolone Resistance and Extended-Spectrum Beta-Lactamases among Clinical Enterobacteriaceae Isolates from a Tertiary Hospital in Katsina, Nigeria - Hussaini Mujahid; Dawud Ibrahim; Ibrahim Bashir; Muhammadu Abdullah Ibrahim; Junaidu Isah Goronyo; Yusuf Mansur (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt